MANAGEMENT ANALYSIS THE RELATIONSHIP MERCHANT MIDDLEMENT TO SUPPLIER AND CUSTOMER PEPPER IN MERANCANG ILIR VILLAGE, EAST BORNEO, INDONESIA - Daulika, Putri (Socio-Economics/Agribusiness Department, 2024)
The purpose of this study was to: 1) Describe the status and role of middlement in the trade and marketing of pepper, 2) Describes the purchasing system is being run, 3) Describes how to set the price, 4) Explaining SRM and CRM performed by middlement in maintaining a relationship with supplier and customer. This research used qualitative that have descriptive explanation characteristic. The researcher used participant-observation (participant observation), interviews and photos as the tools of collecting data. The determination participants and key informant for this research used snowball sampling techniques, with one participant and four key informants. This research used qualitative data that have descriptive explanation characteristic, are analyzed descriptively. The results of this study indicate that: 1) Status as a peppers collector in the pepper trading and marketing activities was the person who runs three roles at once, 2) Purchasing system was done by the collectors by collecting and looking for pepper from farmers (suppliers) to be purchased in accordance with market prices, and payment usually by giving cash advance prior to the harvest or by paid upon trading activities are taking place, 3) The system in pricing is applied and executed by an intermediary trader, namely the Mark-Up Pricing Method, amounting to IDR 2,000.00/kg pepper from the price given to customers, 4) The relationship management of supplier and customer who performed by collectors consist of: CRM activity (real relationship with customers and customer satisfaction), and SRM (commitment, communication, honestly, discussion, and sharing of information).